A comprehensive review of state-of-the-art optical methods for methane gas detection - Khandaker, Sayma; Nurulain Nadhirah, Shaipizaman; Hasan, Md Mahmudul; Mohd Amir Shahlan, Mohd Aspar; Hadi, Manap (Universiti Putra Malaysia, 2024)
Methane (CH₄), a potent greenhouse gas, significantly contributes to climate change and global warming. Its impact over 100 years surpasses carbon dioxide (CO₂) by 28 times. Addressing methane emissions, particularly from oil and gas production activities such as transmission pipelines, is imperative. One promising avenue is the development of reliable sensors to detect and mitigate methane leaks and prevent hazardous issues. Optical-based methods present notable advantages, including versatility and remote operation, making them pivotal in this endeavor. This review article provides a concise overview of optical-based methane identification technologies, encompassing sensing materials, absorption spectra, operational mechanisms, and recent advancements. Potential perspectives are explored, and inferences from this assessment are also derived. Emphasizing the significance of optical fiber-based methane detection methods, the authors advocate for further research to support ongoing efforts and foster innovation in this critical area.